EFFECT AND PREVENTION OF DRUG/SUBSTANCE ABUSE AMONG SECONDARY SCHOOL STUDENTS IN NIGERIA: REPORT OF 2022 WORLD MENTAL HEALTH DAY IN ABEOKUTA OGUN STATE, SOUTH WEST, NIGERIA. - Salako, Larry; Nurudeen Oyekola Ibrahim; Sunday Mauton Amosu (Student’s Journal of Health Research Africa, 2023)
Background: Several studies have shown a high prevalence of drug and substance abuse across the Universities and Secondary schools in Nigeria. AIM: To conduct an awareness program among Secondary School students in commemoration of Mental Health Day 2022 Methodology: Three (3) Secondary Schools were selected within Abeokuta, the capital of Ogun state, Southwest Nigeria. An awareness program was organized through health talks on the effect and prevention of drug/substance abuse. It was a didactic and interactive session with the students. Result: Some students who abuse substances were discovered and a drug abuse ring was also discovered. Through the management of schools visited there was easier networking with other schools and appeal for regular visits solicited by the schools. Conclusion: Appreciation to the Sebastian Family and the University of Wisconsin for their great work on mental health advocacy globally. Likewise, all the staff of the visited schools are highly appreciated for their cooperation, while not unmindful of the efforts of all team members who have put in their best to see that this year’s program was successful. Recommendation: There is a need for continuous sensitization to other schools and working with school authorities in the area of rehabilitation of identified drug/substance abusers.